Monitoring of Territories in the Management System of the Hotel Complex Construction - Shchepak, Vira; Senenko, Natalia; Senenko, Inna; Nesterenko, Svitlana (International Journal of Engineering and Technology, 2018)
The aim of the work was to study the management system for the construction of a hotel complex, to develop a structural and logical model of a management system, to study the monitoring of territories, to assess the ecological state of territories for choosing a location for the construction of a hotel complex.In the process of preparing the publication, a systematic approach and an integrated assessment of the territories characteristics were used.The study determined that the construction of hotels is formed under the influence of a significant number of different factors of the external and internal environment and is a complicated process.It is necessary to take into account the tendencies of customer demand during the formation of the construction management system. At present, among the basic wishes, there is a need for recreation in ecologically clean areas.Therefore, it is proposed to consider the management system for the construction of a hotel complex as an extended system, which consists of four main components. These are territories for the location of the complex, design organizations, contractors and investors.In the developed structural-logical model of the management system for the construction of a hotel complex, special attention was paid to the choice of the territory for construction. It was suggested to make a choice on the basis of assessing the ecological state of the territories. The main characteristics of the assessment are the ecological stability of the territories, anthropogenic load, plowing of territories, agricultural development of territories and recreational capacity. In this paper, the assessment of the ecological status of the territories of the Poltava region districts was carried out and integrated indicators were determined. According to the results of the research, three groups of ecological stability of the territories were identified. The first two groups have a moderate and medium ecological stability of the territories. They are attractive for investment for the construction of a hotel and restaurant. Further research should be directed to the assessment of the quality of soils, which will enable to increase the efficiency of the use of territories in the construction of hotel complex.Â Â Â